Structural change, expanding informality and labour productivity growth in Russia - Ilya B. Voskoboynikov (Bank of Finland, Institute for Economies in Transition (BOFIT), 2017)
Intensive growth, structural change and expanding informality has characterized many developing and emerging economies in recent decades. Yet most empirical investigations into the relationship between structural change and productivity growth overlook informality. This paper includes the informal sector in an analysis of the effects of structural changes in the Russian economy on aggre-gate labour productivity growth. Using a newly developed dataset for 34 industries covering the period 1995–2012 and applying three alternative approaches, aggregate labour productivity growth is decomposed into intra-industry and inter-industry contributions. All three approaches show that the overall contribution of structural change is growth-enhancing, significant and attenuating over time. Labour reallocation from the formal sector to the informal sector tends to reduce growth through the extension of informal activities with low productivity levels. Sectoral labour reallocation effects are found to be highly sensitive to the methods applied.
URN:NBN:fi:bof-201711291674
Keywords: O11; O17; C82; N14; 330